The Relationship between the use of ATS and the level of satisfaction of the family of patients in the emergency room at the Banjar City Hospital - Asri Aprilia Rohman; Yoga Ginanjar (Jurnal Vocational Nursing Sciences (VNUS), 2019)
The Australasian Triage Scale (ATS) method is one of several triage systems used in Indonesia for the assessment of clinical emergencies. Emergency Department (IGD) as the leading service provider also takes part in the realization of hospital customer satisfaction. Siboro (2014) says that customer satisfaction is determined by the whole series of services, including patient registration/admission, doctors, nurses, food, medicines, facilities and equipment, hospital physical facilities and administrative services (Siboro, 2014). Based on information compiled by Warta Priangan on March 15, 2019, a Banjar resident complained about the service at the Emergency Room at Banjar City Hospital. One of the patient's families admitted that they were disappointed with the government hospital services due to the lack of response from nurses and doctors in dealing with their sick child. These complaints indicate that patients are not satisfied with nursing services and can affect the quality of hospital services. The purpose of this study was to determine the relationship between the use of ATS triage and the level of patient satisfaction in the ER at the Banjar City Hospital. The type of research used is a descriptive correlation design with a cross-sectional design which aims to determine the relationship between the variables studied. The total population is 19,661 people. The sampling technique of Non-Probability Sampling is accidental sampling with a sample size of 99 people. The instrument in this study used a questionnaire. The results of hypothesis testing using the chi-square obtained p-value of 0.000, smaller than 0.05, which means Ho is rejected and Ha is accepted so the decision is that there is a relationship between the use of ATS and the level of satisfaction of the patient's family in the Emergency Room of the Banjar City Hospital